2018
DOI: 10.29271/jcpsp.2018.05.361
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Predictability Of Lower Uterine Segment Cesarean Section Scar Thickness

Abstract: Sonographic assessment of a uterine scar has a practical application to determine the thickness of previous scar, and assess its integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…16 Many studies in literature assessed the lower uterine segment even before conception. 17 The benefit of performing ultrasound at later gestation is that lower uterine segment has been developed and the presenting part is engaged in the pelvis. Although not many studies are available regarding uterine scar status especially in non-pregnant condition, Alfred Warionch in his study in 1967, using hysterography concluded that as the number of caesarean sections increase, the scars become thinner.…”
Section: Discussionmentioning
confidence: 99%
“…16 Many studies in literature assessed the lower uterine segment even before conception. 17 The benefit of performing ultrasound at later gestation is that lower uterine segment has been developed and the presenting part is engaged in the pelvis. Although not many studies are available regarding uterine scar status especially in non-pregnant condition, Alfred Warionch in his study in 1967, using hysterography concluded that as the number of caesarean sections increase, the scars become thinner.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent pregnancies, thin LUS is likely to rupture. 12,13 According to Jordans et al, there is an inverse relationship between LUS thickness and scar rupture, with a LUS thickness of 3.5mm being protective against uterine rupture. 14 A meta-analysis found a strong relationship between the degree of LUS thinning measured near term and the risk of uterine scar defect at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors report that a distance of 3.1 to 5.1 mm from the bladder wall to the amnion has a 96% sensitivity and a 63% specificity for the occurrence of a uterine defect (dehiscence, rupture). There is insufficient evidence to recommend the routine ultrasound assessment of uterine scar integrity [ 21 , 22 ]. The cut-off value for the thickness of the uterine scar on the lower uterine segment measured by transvaginal sonography is not established.…”
Section: Tolac – Between Risk and Benefitsmentioning
confidence: 99%